Alkaloids, Biosynthesis and Their Applications - Tyagi, Renu; Kalani, Rekha; Pareek, Chandresh (International Journal on Orange Technologies, 2023)
Alkaloids are a class of basic, naturally occurring organic compounds that contain at least one nitrogen atom. This group also includes some related compounds with neutral[2] and even weakly acidic properties.[3] Some synthetic compounds of similar structure may also be termed alkaloids.[4] In addition to carbon, hydrogen and nitrogen, alkaloids may also contain oxygen, sulfur and, more rarely, other elements such as chlorine, bromine, and phosphorus.[5] Alkaloids are produced by a large variety of organisms including bacteria, fungi, plants, and animals.[6] They can be purified from crude extracts of these organisms by acid-base extraction, or solvent extractions followed by silica-gel column chromatography.[7] Alkaloids have a wide range of pharmacological activities including antimalarial (e.g. quinine), antiasthma (e.g. ephedrine), anticancer (e.g. homoharringtonine),[8] cholinomimetic (e.g. galantamine),[9] vasodilatory (e.g. vincamine), antiarrhythmic (e.g. quinidine), analgesic (e.g. morphine),[10] antibacterial (e.g. chelerythrine),[11] and antihyperglycemic activities (e.g. piperine).[12] [failed verification] Many have found use in traditional or modern medicine, or as starting points for drug discovery. Other alkaloids possess psychotropic (e.g. psilocin) and stimulant activities (e.g. cocaine, caffeine, nicotine, theobromine),[13] and have been used in entheogenic rituals or as recreational drugs. Alkaloids can be toxic too (e.g. atropine, tubocurarine).[14] Although alkaloids act on a diversity of metabolic systems in humans and other animals, they almost uniformly evoke a bitter taste.[15]